Pengaruh Komitmen Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Graha Mandiri Barata Medan - Saragih, Zainul; Hermansyur, Muhammad; Sunaryo (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This research aims to find out the influence of organizational commitment to performance through job satisfaction as an intervening variable in PT. Graha Mandiri Barata Medan. The population in this study amounted to 300 people with a sample number of 171 people. The sampling method is randome sampling.The data obtained is then processed using spss statistics tool version 22. Data analysis techniques in this study include reliability tests, validity tests, classical assumption tests (multicollinearity tests, normality tests, and heteroskedasticity tests), statistical tests (determination coefficient tests (R2), individual parameter significance tests (t tests), simultaneous significance tests (f tests), and path analysis.The results showed that organizational commitment has a positive and significant effect on job satisfaction. Job satisfaction has a positive but insignificant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Job satisfaction cannot mediate between variables of an organization's commitment to employee performance.